PENGGUNAAN METODE PROJECTED UNIT CREDIT PADA ASURANSI PENSIUN GABUNGAN MODEL VASICEK DAN CIR - WILLIEARDAN, FARREL; WIDANA, I NYOMAN; GAUTAMA, I PUTU WINADA (E-Jurnal Matematika, 2023)
Pension plan is an investment plan offered by employee company or life insurance companies to help create retirement funds. This research attempts to estimate the normal cost that participants must pay as well as the actuarial liability that must be paid by the insurance company to the participants using Projected Unit Credit method. Projected Unit Credit method uses the present value of the pension benefit and divided it by participant’s years of service. stochastic interest such as the Vasicek model and the CIR model will be used as a comparison. The result of this research is that the estimation of the normal cost and actuarial liability with the CIR model is smaller than the Vasicek model in the initial year, but the CIR model experience a greater increase than the Vasicek model which causes the normal cost and actuarial liability with the CIR model more expensive than the Vasicek model at the end of the contract. Both premiums and the actuarial liabilities increase as participants age .